Molding composition, molded body, and method for suppressing gas generation
By using pore coordination multi-body containing metal ions and organic coordination agents during the plastic resin molding process, the problem of gas generation during the plastic resin molding process is solved, higher molding accuracy and sealing are achieved, and environmental pollution and mold maintenance costs are reduced.
Patent Information
- Application Number
- JP2025010331
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-23
AI Technical Summary
The prior art is difficult to effectively suppress the gas generated by plastic resin during molding, resulting in reduced precision of molded bodies, poor sealing properties and environmental pollution.
Using pore coordination multi-body with plastic resin, rubber and sealing material, the pore structure is optimized to adsorb and suppress gas generation by adjusting the radius of metal ions and the acid dissociation constant of the gas.
It significantly reduces gas generation during molding, improves the accuracy and sealing of the molded body, reduces environmental pollution, and reduces mold corrosion and maintenance frequency.
Smart Images

Figure 2025066803000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a molding composition and a molded article. [Background technology]
[0002] In recent years, when plastic resin molded products are used for bearings and other applications, the need for high precision is increasing. On the other hand, plastic resin molded articles are used for applications such as joints for water heaters. In such cases, there is a demand for higher strength through void reduction and higher precision in the sealing area. Poor appearance of the molded product surface due to gas generation from plastic resin (e.g., discoloration and and welds), accumulation of the above gas components in the mold during molding, corrosion caused by the above gas, etc. There is a need to improve this problem. Gas generated from plastic resins from molded products can cause environmental degradation (especially in the work environment) In sensitive semiconductor-related production sites, problems such as environmental deterioration caused by the generation of the above gases from parts, etc. There is a demand for improving the following. Various studies have been conducted to improve this problem, but there is still room for improvement.
[0003] The method of suppressing the generation of the above gases is to first add a sufficient number of gas vents to the mold, There is a method to suppress the generation of gas by installing a gas suction device on the molding machine. If the plastic resin is polyphenylsulfide (PPS), it must not contain any oxidizing substances. Polyphenyl sulfide is heated under the conditions of the presence of oxidative crosslinking. There is a method to greatly reduce the amount of volatile gas components generated by However, neither method was able to sufficiently suppress the generation of gas. In particular, in the above-mentioned oxidation crosslinking treatment method, the degree of thermal oxidation treatment is large, When pelletized PPS is melted after thermal oxidation treatment, gelation occurs and the molded product becomes unstable. This leads to other problems.
[0004] Another method for suppressing gas generation is to adsorb the gas in the plastic resin. This method involves, for example, adding metal compounds such as molybdenum and tungsten to the plastic. A method of adding zinc oxide to plastic resin (Patent Document 3), and a method of adding zinc oxide to plastic resin (Patent Document 4), and a method of adding a hydrotalcite substance to a plastic resin (Patent Document Reference 5), a method of adding PAN-based carbon fibers to plastic resin (Patent Document 6), Zeon A method of adding a Lewis porous body to a plastic resin (Patent Document 7), There is a method of adding a porous coordination polymer having an acid value (Patent Document 8). Although the method of adsorbing the substance in a stick resin has a certain degree of effectiveness, further improvements are needed. be. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 63-207827 [Patent Document 2] Japanese Patent Application Publication No. 197422 / 1983 [Patent Document 3] Patent No. 3245253 [Patent Document 4] Re-tabled publication No. 2005-037924 [Patent Document 5] Patent No. 3235035 [Patent Document 6] JP 2017-190426 A [Patent Document 7] JP 2016-132710 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, the method for suppressing the generation of gas from base materials such as plastic resins is Although each of these methods has a certain degree of effectiveness, there is still room for further improvement. Therefore, the object of the present invention is to provide a method for manufacturing a sealant comprising a plastic resin, a rubber, and a sealant. A molding composition capable of suppressing the generation of gas to the outside from one or more base materials selected from the group The object of the present invention is to provide a composition and a molded article. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors have discovered a method for producing a metal ion having a specific radius. The porous coordination polymer containing the metal ion and organic ligand having the above structure is combined with a base material. It has been found that, when these two components are combined, the resulting molding composition can solve the above problems, and the present invention has been completed. This is what I came to do. That is, the present invention is as follows.
[0008] (1) Porous coordination polymers containing metal ions and organic ligands, and plastic resins, rubbers, and one or more base materials selected from the group consisting of a sealing material, The coordination polymer and the base material are molding compositions each satisfying the following condition (A) or (B): Composition. (A) when the acid dissociation constant of the gas derived from the base material is 15.7 or less, the porous The radius of the metal ion in the coordination polymer is 62×10 -12m or less. (B) when the acid dissociation constant of the gas derived from the base material is 16.2 or less, the porous The radius of the metal ion in the coordination polymer is 68×10 -12 m or more.
[0009] (2) The metal ion is Ag(I), Al(III), Be(II), Ca(II), Cd (II), Ce(III), Co(III), Co(II), Cr(III), Cu(I I), Cu(I), Dy(III), Er(III), Eu(III), Fe(III) , Fe(II), Ga(III), Gd(III), Ho(III), In(III), Li(I), Mg(II), Mn(III), Mo(III), Nd(III), Ni( II), Sc(III), Sm(III), Sn(II), Tb(III), Tm(II I), Ti(IV), V(III), W(IV), Y(III), Yb(III), Zn (II), Pd(II), Au(I), Tl(I), Hg(I), Pt(I) and Zr( IV) A molding composition which is one or more selected from the group consisting of:
[0010] (3) A molded article of the above molding composition.
[0011] (4) One or more base materials selected from the group consisting of plastic resins, rubbers, and sealing materials By blending a porous coordination polymer containing metal ions and organic ligands into the silicon material, A method for suppressing gas generation originating from the base material, comprising the steps of: and a method in which the base material satisfies the following condition (A) or (B), respectively: (A) when the acid dissociation constant of the gas derived from the base material is 16.6 or less, the porous The radius of the metal ion in the coordination polymer is 62×10 -12 m or less. (B) when the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous The radius of the metal ion in the coordination polymer is 68×10 -12 m or more. Effect of the Invention
[0012] According to the present invention, a material selected from the group consisting of plastic resins, rubbers, and sealants is Molding composition and molded body capable of suppressing gas generation from one or more base materials to the outside It is possible to provide. [Brief description of the drawings]
[0013] [Figure 1] As an example of analysis by pyrolysis gas chromatography, the figure shows a chromatogram of the analysis results of aromatic polyamide resin (PA6T). [Diagram 2] A diagram showing the relationship between the acid dissociation constant of a gas component and the ionic radius of a metal ion constituting a porous coordination polymer, with a threshold gas adsorption rate of 15%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described. The embodiments are merely examples for explaining the present invention, and the present invention is not limited to these embodiments. It is not something that can be achieved.
[0015] Porous coordination polymers containing metal ions and organic ligands, plastic resins, rubbers and one or more base materials selected from the group consisting of sealing materials, The reactive coordination polymer and the base material each satisfy the following condition (A) or (B). (A) when the acid dissociation constant of the gas derived from the base material is 16.6 or less, the porous The radius of the metal ion in the coordination polymer is 62×10 -12 m or less. (B) when the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous The radius of the metal ion in the coordination polymer is 68×10 -12 m or more.
[0016] The molding composition of the present embodiment is obtained by combining the above-mentioned porous coordination polymer and a base material. This makes it possible to suppress the generation of gas originating from the base material to the outside. More specifically, the gases that are generated from the base material are not limited to gases that are generated from impurities in the base material. Ingredients that may be included as materials (e.g., polymerization agents during resin synthesis, catalyst residues), and base materials and other materials that may be included in the molding composition (e.g., hardeners, inorganic fillers, plasticizers, antioxidants, etc. gas derived from interactions with chemicals such as fluorine-containing compounds, ultraviolet absorbers, light stabilizers, heat stabilizers, and flame retardants. The gas referred to here may be, for example, a gas generated during the process of heating and molding a molding composition containing a base material. The gas may be generated by decomposition of the above-mentioned components, and may be vacant over time in the form of a molded article. The gas may be a gas generated by decomposition of the above-mentioned components by contact with air or the like. When the molding composition is used for molding, the deterioration of precision due to generated gas can be suppressed, and the It is possible to suppress the deterioration of strength due to damage, etc., and to suppress environmental deterioration such as cleanliness, As a result, the molding composition can suppress the corrosion of the mold during molding. The objective of this project is to improve the quality of the molded product and reduce costs by reducing the frequency of mold maintenance, etc. The type of gas generated from the molding composition can be determined by analyzing the gas. Identify and identify the substances contained in the base material and other molding compositions that cause the gas to be generated. Considering the types of components that can be obtained and the conditions under which the gas is generated, the It is possible to distinguish whether the gas is coming from the source or not.
[0017] In this embodiment, the ionic radius of the porous coordination polymer is determined by the Diploma Program Collection of academic materials, Shannon et al., Acta A 32 (1976) 751., http: / / pmsl.planet.sci.kobe-ua They are classified in accordance with the contents listed at c.jp / ~seto / ?page_id=51&lang=ja, etc.
[0018] (Porous coordination polymer) The porous coordination polymer contains metal ions and organic ligands. For example, the metal ion is adsorbed on an organic ligand. It is an organic ligand that can bind to ions. Porous coordination polymers are also called MOFs (Metal-Organic Frameworks). ganic Framework) or PCP (Porous Coordination It is also called polymer. The porous coordination polymer has, for example, a large number of pores in the macropore or mesopore region, and the pore diameter (pore The diameter of the pores is determined by the crystal structure, so the pores have a uniform diameter. The molecule can be made from the base material by controlling the affinity through the length and chemical structure of the organic ligand. The gas generating capacity can be increased and the gas can be packed closely. The average pore size of the porous coordination polymer is preferably equal to or larger than the molecular size of the generated gas. The specific surface area of the polymer, measured by the BET method, is 400 m 2 It is preferable that the molecular weight is 1 / g or more. The average pore size of the porous coordination polymer can be determined from the gas adsorption isotherm measured by the BET method. .
[0019] (Metal ions) From the viewpoint of suppressing the generation of gas derived from the base material to the outside, the acid dissociation constant of the gas is When is less than 16.0, the radius of the metal ion in the porous coordination polymer is 62×10 -12 m or less In addition, when the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous structure The radius of the metal ion in the coordinate polymer is 68×10 -12 m or more. Metal ion radius is 62×10 -12 Metal ions below m include Al(III), Be (II), Cr(III), Fe(III), Fe(II), Ga(III), Ti(I V) and others. On the other hand, the radius of a metal ion is 68×10 -12 Metal ions with m or more include Ag(I). , Be(II), Ca(II), Cd(II), Ce(III), Co(III), Co (II), Cu(II), Cu(I), Dy(III), Er(III), Eu(III ), Ga(III), Gd(III), Ho(III), In(III), Li(I), Mg(II), Mn(III), Mo(III), Nd(III), Ni(II), Sc (III), Sm(III), Sn(II), Tb(III), Tm(III), V(I II), W(IV), Y(III), Yb(III), Zn(II), Pd(II), A Examples include U(I), Tl(I), Hg(I), Pt(I), and Zr(IV).
[0020] (organic ligand) The organic ligand is preferably a bridging ligand capable of bridging to a metal ion. Examples of such compounds include 2-methylimidazole, terephthalic acid, and 2,5-dihydroxyterephthalic acid. Taric acid, 1,4-naphthalenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 4, 4′-Biphenyldicarboxylic acid, 4,4″-p-terphenyldicarboxylic acid, isophthalic acid Acid, 1,3,5-benzenetricarboxylic acid, 1,3,5-tri-4-carboxyl Phenylbenzene, methylimidazole, 4,4'-biphenyldicarboxylic acid, fumaric acid , naphthalenedicarboxylic acid, hexaazatriphenylene, 2,5-dihydroxybenzoic acid , Trimesic acid, 5-cyano-benzenedicarboxylic acid, 5-ethyl-1,3-benzodicarboxylic acid carboxylic acid, terephenyl-3,3',5,5'-tetracarboxylic acid, 9,10-anthracene dicarboxylic acid, imidazole, 2,2'-diamino-4,4'-stilbene dicarboxylic acid Acid, 2,2′-dinitro-stilbenedicarboxylic acid, 2,5-dihydroxyterephthalic acid , 3,3′,5,5′-tetracarboxydiphenylmethane, 1,2,4,5-tetrakis 4,4′,4″-s-triazine-2,4,6 TRAIL-TRIBENZOIC ACID, 2-HYDROXYTEREPHTHALIC ACID, BIPHENYL-3,3',5,5' -Tetracarboxylic acid, biphenyl-3,4,5-tricarboxylic acid, 5-bromoisophthalic acid Acid, Malonic Acid, 5-Cyano-Benzenedicarboxylic Acid, 5-Ethyl-1,3-Benzodicarbo Acid, terephenyl-3,3″,5,5″tetracarboxylic acid, 9,10-anthracene di Carboxylic acid, imidazole, 2,2′-diamino-4,4-stilbenedicarboxylic acid, 2 ,2′-Dinitro-stilbenedicarboxylic acid, 2,5-dihydroxyterephthalic acid, 3, 3',5,5'-Tetracarboxydiphenylmethane, 1,2,4,5-Tetrakis(4- Carboxyphenyl)benzene, 4,4′,4″-s-triazine-2,4,6 trail -Tribenzoic acid, 2-hydroxyterephthalic acid, biphenyl-3,3′,5,5′-tetra Carboxylic acid, biphenyl-3,4',5'-tricarboxylic acid, 5-bromoisophthalic acid, malonic acid, etc.
[0021] In the method for producing a composition for a molded body, a porous coordination polymer is attached to the surface or inside of pores. After removing any residual substances present, the porous coordination polymer is composited to the base material. If residual materials are present, they may narrow or completely destroy the pores. There is a risk that the generated gas may become difficult to inject into the pores of the porous coordination polymer. As a method for removing the residue, for example, a method of washing the porous coordination polymer with a solvent can be mentioned. Examples of the solvent used for washing include water, methanol, THF, and DMF. The solvent is preferably water and / or methanol. Or, in the case of methanol, the molecular diameter of the solvent is small, so the solvent enters the pores of the porous coordination polymer. The residual substances in the pores can be easily removed. In the above process, the porous coordination polymer may be immersed in the solvent for a long period of time. The immersion time is 12 hours or more. Preferably, the reaction time is 1 hour or more, and more preferably, 24 hours or more. As a method for removing the substances, a method in which residual substances are desorbed by heat treatment can be mentioned. If the unreacted substances or impurities are organic and you want to remove the organic substances, It is preferable to carry out the heat treatment in air. If it is desired to remove volatile substances, it is preferable to carry out vacuum heat treatment. After cleaning with a solvent, the solvent is completely removed by heat treatment. A method for removing the ions is preferred.
[0022] (Base material) The base material is selected from the group consisting of plastic resins, rubbers, and sealants. In addition, inorganic fillers, plasticizers, weather resistance additives, etc. may be added as necessary. There are no particular limitations on the additives that are generally added to the base material. The gas derived from the base material is generated from these compounded materials. The acid dissociation constant of a gas is as follows: If the general formula of the acid is HA and the solvent is Hsol, the dissociation equilibrium reaction is It becomes like this.
number
number
[0023] (Plastic Resin) The plastic resin may include one or more types of resin. The resin may be, for example, a thermoplastic resin. Thermoplastic resins include polyethylene resin, polypropylene resin, and thermosetting resin. Polypropylene resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyvinyl acetate resin , polystyrene resin, AS resin, ABS resin, methacrylic resin, polyvinyl alcohol resin resins, EVA resins, aromatic polyamide resins and polyamide 66, Reacetal resin, polycarbonate resin, polyphenylene ether resin, polyethylene Terephthalate resin, polybutylene terephthalate resin, fluororesin, polyphenylene sulfide resin, polysulfone resin, polyarylate resin, polyetherimide resin, Polyethersulfone resin, polyetherketone resin, liquid crystal polyester resin, thermoplastic polyester Examples of thermosetting resins include elastomeric imide resins and thermoplastic polyurethane resins. epoxy resin, unsaturated polyester resin, phenol resin, urea resin, melamine resin, Lukid resin, silicone resin, polyimide resin, polyurethane resin, vinyl ester resin , diallyl phthalate resin, furan resin, polyamino bismaleimide resin, casein resin , epoxy acrylate resin, urethane acrylate resin, polyurea resin, benzoxy Sazin resin, oxetane resin, xylene resin, dicyclopentadiene resin, and episul Among these, from the viewpoint of further reducing gas derived from the base material, From aromatic polyamide resins and polyamide resins such as polyamide 66 and polyphenylene Preferred are aromatic polyamide resins and polyphenylene sulfide resins. A resin such as ethylenediaminetetraacetate is more preferred.
[0024] (Rubber) Examples of rubbers include artificial rubber and natural rubber. Examples of artificial rubbers include poly Butadiene, polyisoprene, styrene-butadiene random copolymers and block copolymers Polymers, hydrogenated block copolymers, acrylonitrile-butadiene copolymers, butadiene Diene-based rubbers such as diene-isoprene copolymers, and random copolymers of ethylene and propylene ethylene-butene random and block copolymers; Copolymers of ethylene and α-olefins, ethylene-acrylic acid, ethylene-methacrylic Ethylene-unsaturated carboxylic acid copolymers, ethylene-acrylic acid esters, ethylene -Methacrylic acid ester and other ethylene-unsaturated carboxylic acid ester copolymers, unsaturated carboxylic acid ester copolymers Part of the acrylic acid is a metal salt. Ethylene-acrylic acid-metal salt of acrylic acid, ethylene-methacrylic acid Ethylene-unsaturated carboxylic acid-unsaturated carboxylic acid gold salts such as methacrylic acid-methacrylic acid metal salts Metal salt copolymer, acrylate-butadiene copolymer, butyl acrylate-butadiene acrylic elastomers such as ethylene-vinyl acetate copolymers, and ethylene-fatty acid vinyl copolymers such as ethylene-vinyl acetate. copolymers with ethylene, ethylene-propylene-ethylidene norbornene copolymers, ethylene - Ethylene-propylene non-conjugated diene terpolymers such as propylene-hexadiene copolymers Examples of such materials include polyethylene terephthalate, butylene-isoprene copolymers, chlorinated polyethylene, and modified products thereof. These rubbers may be used alone or in combination of two or more.
[0025] (Silicone material) Examples of the sealant include silicone sealant and modified silicone sealant. sealing materials, polyurethane-based sealants (e.g., acrylic urethane sealants), Acrylate-based sealant, polysulfide-based sealant, polyisobutylene These sealants can be used alone or in combination of two or more types. The above are used in combination.
[0026] (Inorganic filler) The molding composition may contain an inorganic filler from the viewpoint of improving mechanical properties. As the filler, a known inorganic filler is used, for example, a particulate inorganic filler, a fibrous inorganic filler, etc. Examples of particulate inorganic fillers include fillers in the form of granules, and scaly or plate-like inorganic fillers. Even if the particulate inorganic filler has a micron size, the particulate inorganic filler has a nano size. The particulate inorganic filler having a micron size may be, for example, carbon. Calcium oxide particles, silica particles, glass beads, titanium oxide particles, zinc oxide particles, titanium potassium phosphate particles, titania particles, monoclinic titania particles, calcium phosphate particles, wallace Examples include tonite, vermiculite, Shirasu balloons, and glass balloons. Examples of particulate inorganic fillers having a particle size include nano-titanium oxide, nano-silica, and carbon. Examples of inorganic fillers include cellulose black and carbon filler. Inorganic fillers can be used alone or in combination. The above are used in combination. Among these, the particulate inorganic filler is a functional sustained release liquid From the viewpoint of superior sustained release properties (especially for small animal control agents), the particles are potassium titanate. From the viewpoint of not adversely affecting the appearance of the molded article, the fibrous inorganic filler is preferably 0.05 A fibrous inorganic filler with an average fiber diameter of 10 μm and an average fiber length of 3 to 150 μm. It is preferable that the average fiber diameter is 0.1 to 7 μm and the average fiber length is 5 to 50 μm. It is more preferable that the fibrous inorganic filler is a fibrous inorganic filler having the above structure. Examples of the fibrous inorganic filler include The inorganic filler may be a fibrous inorganic filler having a micron size, and the inorganic filler may be a fibrous inorganic filler having a nano size. Examples of fibrous inorganic fillers having a micron size include: Glass fiber, carbon fiber, graphite fiber, aramid fiber, vinylon fiber, polyamide fiber, poly Ester fiber, cotton, hemp fiber, kenaf fiber, bamboo fiber, rayon, steel fiber, aluminum Aluminum fiber, gypsum fiber, potassium 4-titanate fiber, potassium 6-titanate fiber, potassium 8-titanate fiber Aluminium fiber, titania fiber, monoclinic titania fiber, silica fiber, wollastonite, xono Examples of fibrous inorganic fillers having nano sizes include carbon fiber. Bon fiber, carbon nanotube, fullerene, cotton fibril, silicon nitride Examples of the whiskers include isker, alumina whiskers, silicon carbide whiskers, and nickel whiskers. These fibrous inorganic fillers may be used alone or in combination of two or more. Examples of the scale-like or plate-like inorganic filler include scale-like or plate-like inorganic fillers having a micron size. The inorganic filler may be a granular inorganic filler or a scale-like or plate-like inorganic filler having a nano-size. Examples of the scale-like or plate-like inorganic filler having a micron size include talc, kaolin, etc. clay, mica (synthetic or natural), glass flakes, aragonite, sulfuric acid Calcium, aluminum hydroxide, potassium titanate, potassium lithium titanate, titanium Examples of suitable alumina include potassium magnesium phosphate, sericite, plate-like alumina, and boron nitride. Examples of the scaly or plate-like inorganic filler having a certain size include organic montmorillonite. , swellable synthetic mica, graphite, etc. Scale-like inorganic fillers are They may be used alone or in combination of two or more. The inorganic filler may be used as it is. From the viewpoint of improving the interfacial adhesion with resin and further improving the mechanical properties, Silane coupling agents such as minosilane, epoxysilane, and acrylic silane, or titanates The polymer may be used after being surface-treated with a surface treatment agent such as a coupling agent.
[0027] (Plasticizer) The molding composition contains a plasticizer from the viewpoint of further improving the processability and flexibility of the molded body. Examples of the plasticizer include carboxylate derivatives and phosphate derivatives. , phosphazene derivatives, carboxylic acid amide derivatives, sulfonic acid ester derivatives, and sulfur The plasticizer may be one type alone or two or more types in combination. Used.
[0028] Examples of the carboxylate derivatives include those having a hydroxyl group, a nitro group, an amino group, and an epoxy group. , alkyl esters of various carboxylic acids which may be substituted with halogens, etc., and aromatic esters Specific examples of the carboxylate derivatives include dimethylphthalate. phthalate, diethyl phthalate, di-n-octyl phthalate, diphenyl phthalate, Dimethylphthalate, Dimethoxyethylphthalate, 4,5-epoxyhexahydrophthalic acid Di(2-ethylhexyl), 4,5-epoxycyclohexahydrophthalic acid di(7,8- Epoxy-2-octenyl), 4,5-epoxycyclohexahydrophthalic acid di(9,1 0-epoxyoctadecyl), 4,5-epoxycyclohexahydrophthalic acid di(10, 11-epoxyundecyl), di(tetrahydrofurfuryloxyethyl) phthalate, various Phthalates such as mixed phthalate esters and ethylene oxide adducts of mixed phthalate esters Ester derivatives, isophthalic acid ester derivatives, tetrahydrophthalic acid ester derivatives, Butoxyethyl parahydroxybenzoate, cyclohexyloxyethyl parahydroxybenzoate 2-Ethylhexyl parahydroxybenzoate, ω-alkyl Hydroxybenzoic acid ester of ethylene oxide, undecyl glycidyl ether Benzoic acid ester derivatives such as trihydroxybenzoic acid adducts, di(tetrahydrobenzoic acid) propionate derivatives such as tetrahydrofurfuryloxyethyl, adipate esters Derivatives, Azelaic acid ester derivatives, Sebacic acid ester derivatives, Dodecanoic acid ester derivatives ester derivatives, maleic ester derivatives, fumaric ester derivatives, trimellitic ester derivatives Derivatives of tert-butyl ether, tri(butoxyethoxyethyl) citrate, di-n-octyl-mono Nonylphenoxyethyl, tri-n-octyl citrate, dioctyl citrate (tetra trahydrofurfuryloxyethyl), trimyristyl citrate, triethyl citrate, etc. citrate derivatives, itaconic acid ester derivatives, tetrahydrofurfur oleate oleic acid ester derivatives such as ethyl oleate, ricinoleic acid ester derivatives, n-butyl lactate , lactic acid (2-ethylhexyl), lactic acid (n-butoxyethoxyethyl), lactic acid (n-octyl) Lactic acid ester derivatives such as (n-decyloxyethoxyethyl), lactic acid (n-decyloxyethoxyethyl), etc. Conductor, di(octoxyethoxyethyl) tartrate, (n-octyl) tartrate (nonylphenol) tartrate derivatives such as di(octoxyethyl) tartrate and di(octoxyethoxyethyl) tartrate; phosphorus Dibutoxyethyl malate, Di(n-butoxyethoxyethyl) malate, Distearate malate malic acid ester derivatives such as octadecenyl isononyl malate, benzyl glycine Salicylic acid ester derivatives such as salicylic acid adducts of diethyl ethers are also included.
[0029] Examples of the phosphate derivatives include trimethyl phosphate and triethyl phosphate. phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, 2-ethyl Diphenylhexyl phosphate, Tributoxyethyl phosphate, Triphenyl phosphate, cresyl diphenyl phosphate, isodecyl diphenyl phosphate phosphate, tricresyl phosphate, trixylenyl phosphate, tri(chloroethyl) R)ho phosphate, xylenyl diphenyl phosphate, and tetrakis(2,4-ditert-butyl phosphate) ethylphenyl)4,4'-biphenylene diphosphonate.
[0030] The phosphazene derivative may be, for example, a cyclic phosphazene derivative represented by the following general formula (1): Examples include compounds. [ka] In the formula, m represents an integer of 3 to 25, and R1 and R2 may be the same or different. and an alkyl group having 1 to 8 carbon atoms, or an alkyl group and / or an aryl group having 1 to 8 carbon atoms. The phosphazene derivative is represented by the formula (1): The linear phosphazene compound may be composed of one type of compound, or may be in the form of a mixture of two or more types. The second embodiment may be configured as follows:
[0031] The phosphazene derivative may be, for example, a linear phosphazene represented by the following general formula (2): Compounds are also included. [ka] In the formula, n represents an integer of 3 to 1000, and R3 and R4 may be the same or different. and an alkyl group having 1 to 8 carbon atoms, or an alkyl group having 1 to 8 carbon atoms and / or represents a phenyl group which may be substituted with an allyl group, and X represents a group -N=P(OR 3 )3. Group -N=P(OR 4 )3, group -N=P(O)(OR 3 ) or the group -N=P(O)(OR 4 ) and Y represents a group -P(OR 3 ) 4, group -P(OR 4 ) 4, group -P(O)(OR 3 )bifurcated is the group -P(O)(OR 4 The phosphazene derivative is a linear phosphazene derivative represented by the formula (2). It may be composed of one type of phosphazene compound or a mixture of two or more types. It may be possible.
[0032] The phosphazene derivative may be a phosphazene derivative represented by the formula (1) or the formula ( 2) R in 1 , R 2 , R 3 , R 4 The alkyl group etc. is eliminated from the aryl group, and the two oxygen atoms are crosslinked. The compound may be a phosphazene compound. [ka] In the formula, r represents 0 or 1, and A represents a divalent group -SO2-, -S-, -O-, or -C (CH3)2-.
[0033] Specific examples of the cyclic phosphazene compound represented by formula (1) include hexaphenoxycyclopentadiene. L-tolyphosphazene, Octaphenoxycyclotetraphosphazene, Decaphenoxycyclotetraphosphazene hexapropoxycyclotriphosphazene, octapropoxycyclotriphosphazene Examples of the cyclopentaphosphazene include cyclotetraphosphazene and decapropoxycyclopentaphosphazene. Specific examples of the linear phosphazene compound represented by formula (2) include linear diphosphazene compounds. Linear phosphazene with propoxy and / or phenoxy groups substituted on chlorophosphazene A specific example of the crosslinked structure represented by formula (3) is 4,4'-sulfonyl Diphenylene (bisphenol-S residue), 4,4'-oxydiphenylene group, 4,4 Examples of these phosphiles include 4,4'-thiodiphenylene and 4,4'-diphenylene. The azene derivatives are those substituted with amino and / or phenylamino groups at any position. These phosphazene derivatives may be used alone or in combination of two or more. It is used.
[0034] Examples of the carboxylic acid amide derivatives include N-cyclohexylbenzoic acid amide. In addition, the sulfonamide derivatives include N-methyl-benzenesulfonamide, N-Ethyl-benzenesulfonamide, N-Butyl-benzenesulfonamide, N-Cyclo N-ethyl-p-toluenesulfonamide, N- Butyl-toluenesulfonamide, N-cyclohexyl-toluenesulfonamide can be done.
[0035] Examples of the sulfonate derivatives include ethyl benzenesulfonate and methanesulfonate. 2-Methoxyethyl methanesulfonate, 2,2,2-trifluoroethyl methanesulfonate, p-Toluene Methyl p-toluenesulfonate, Ethyl p-toluenesulfonate, n-propyl p-toluenesulfonate Ropil and the like.
[0036] Examples of sulfonic acid amide derivatives include N-methylmethanesulfonic acid amide, p-methylmethanesulfonic acid amide, Aminobenzenesulfonamide, p-aminobenzenesulfonamide, o-aminobenzenesulfonamide m-aminobenzenesulfonamide, aniline-4-sulfonic acid amide, 1 -aminobenzene-4-sulfonic acid amide, 1-aminobenzene-4-sulfonamide, Examples thereof include 4-aminobenzenesulfonic acid amide and p-sulfanilic acid amide.
[0037] (Weather resistance additive) The molding composition contains a weather resistance imparting additive from the viewpoint of further improving the weather resistance when left outdoors. The weather resistance additive may contain a hindered phenol-based antioxidant and Antioxidants such as phosphorus-based antioxidants, UV-absorbing light stabilizers, hindered amine-based light stabilizers The material may be one selected from the group consisting of a binder, a stabilizer, and carbon.
[0038] Examples of the hindered phenol-based antioxidants include pentaerythritol tetrakis(II) and tetrakis(III). [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4- hydroxyphenylpropionamide)], bis-[3,3-bis-(4′-hydroxyphenylpropionamide)], 3'-tert-butylphenyl)-butanoic acid]-glycol ester , tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate , thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl ) propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydro 3,3′,3″,5,5′,5″-Hexa-tert- butyl-a,a′,a″-(methylene-2,4,6-triyl)tri-p-cresol, Hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], tetrakis[methylene-3-(3,5-di-tert-butyl-4- hydroxyphenyl)propionate]methane, and methylene-3-(3,5-di- rt-butyl-4-hydroxyphenyl)propionate.
[0039] Examples of phosphorus-based antioxidants include tris(2,4-di-tert-butylphenyl) Phosphite, tris[2-[[2,4,8,10-tetra-tert-butylbenzo [d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amido Tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4 ,4'-diylbisphosphonite, distearyl pentaerythritol diphosphite , bis(2,4-di-tert-butylphenyl)pentaerythritol phosphite, Bis(2,6-di-tert-butyl-4-phenyl)pentaerythritol phosphi and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosph One example is Fighter.
[0040] Examples of ultraviolet absorbents include 2-(2H-benzotriazol-2-yl)-4,6 -Bis(1-methyl-1-phenylethyl)phenol, 2-(2H-benzotriazol (2-yl)-4,6-di-tert-pentylphenol, propanediol , and [(4-methoxyphenyl)-methylene]-dimethyl ester.
[0041] Examples of the hindered amine light stabilizer include N,N',N'',N'''-tetrakis(2-methylphenyl)amine. -(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidine) 4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diazin amine, poly[(6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-trimethyl azine-2,4-diyl)(2,2,6,6-tetramethyl-4-piperidyl)imino] Hexamethylene((2,2,6,6-tetramethyl-4-piperidyl)imino)), bis (2,2,6,6-tetramethyl-4-piperidyl) sebacate, 2,2,4,4-tetramethyl tetramethyl-7-oxa-3,20-diaza-dispiro-[5.1.11.2]-hene Cosan-21-one, propanedioic acid, [(4-methoxyphenyl)-methylene]-, bis (1,2,2,6,6-Pentamethyl-4-piperidinyl) ester, 1,3-benzene Dicarboxamide, N,N-bis(2,2,6,6-tetramethyl-4-piperidinyl ), and 2-ethyl, 2'-ethoxy-oxalanilide.
[0042] The weather resistance additives may be used alone or in combination of two or more. Among them, the weather resistance additive is pentaerythritol tetrakis[3-(3,5-di-t ert-Butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1 ,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionate pionamide)], tris(3,5-di-tert-butyl-4-hydroxybenzyl) Isocyanurate, tris(2,4-di-tert-butylphenyl)phosphite, Tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4 ′-Diylbisphosphonite, bis(2,4-di-tert-butylphenyl)penta Erythritol phosphite, 2-(2H-benzotriazol-2-yl)-4,6- Bis(1-methyl-1-phenylethyl)phenol, 2-ethyl, 2′-ethoxy- Xalanilide, N,N',N'',N'''-tetrakis-(4,6-bis-(butyl-( N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)triazine -2-yl)-4,7-diazadecane-1,10-diamine, poly[(6-(1,1,3 ,3-Tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl)(2, 2,6,6-Tetramethyl-4-piperidyl)imino]hexamethylene((2,2,6, 6-Tetramethyl-4-piperidyl)imino)), 1,3-benzenedicarboxamide and the group consisting of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl) One or more selected from the above may be mentioned.
[0043] In order to further suppress the generation of gas from the base material to the outside, the following formula (4) is used. and one selected from the group consisting of antioxidants represented by the following formula (5): It is also possible to include the above-mentioned antioxidants. When the agent is added to the molding composition, the base material or the porosity caused by heating during molding of the molding composition is reduced. The oxidation and subsequent decomposition of the polymeric coordination compound is further suppressed, and the gas from the base material is prevented from escaping to the outside. In this specification, the formulas (4), (6), (7) and In (9) and (9), the group without a symbol at the bond end represents a methyl group. For example, the following formula ( In 4), three groups without symbols at the bond ends are bonded to the benzene ring. are all methyl groups. [ka] [ka] In the formulas (4) and (5), each R independently represents a hindered phenol group.
[0044] In the molding composition of this embodiment, the generation of gas derived from the base material to the outside is further suppressed. From this perspective, R is a 3,5-di-tert-butyl-4-hydroxyphenyl group or a 4-t It is preferably an ert-butyl-3-hydroxy-2,6-dimethylphenyl group. From a similar perspective, the antioxidant is 1,3,5-tris[(3,5-di-tert-butyl -4-hydroxy-phenyl)methyl]-1,3,5-triazine-2,4,6-triol 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-dimethyl phenyl)methyl]-1,3,5-triazine-2,4,6-trione, and 4-[[3 ,5-Bis[(3,5-di-tert-butyl-4-hydroxyphenyl)methyl]- 2,4,6-trimethyl-phenyl]methyl]-2,6-di-tert-butyl-pheno From the same viewpoint, it is more preferable that the antioxidant is selected from the group consisting of aryl alcohols. is an antioxidant represented by the following formula (6) and an antioxidant represented by the following formula (7). From the same viewpoint, it is particularly preferable that the antioxidant is: It is also preferable to use the above-mentioned preferable antioxidants in combination with a phosphorus-based antioxidant. [ka] [ka]
[0045] In the molding composition of this embodiment, the antioxidant itself is oxidized by heating during molding of the molding composition. In order to suppress the decomposition of the base material and further suppress the generation of gas from the base material to the outside, The melting point of the inhibitor is preferably 150°C or higher, more preferably 200°C or higher, and particularly preferably 220°C or higher. Even more preferred.
[0046] When the molding composition of the present embodiment does not contain the above-mentioned antioxidant, the base in the molding composition The total content of the material and the porous coordination polymer is 60% by mass based on 100% by mass of the molding composition. It is preferably from 70% by mass to 100% by mass, more preferably from 70% by mass to 100% by mass. It is more preferable that the content is 80% by mass or more and 100% by mass or less, and further more preferable that the content is 80% by mass or more and 100% by mass or less. By the total content being within the above range, the amount of gas emitted from the base material to the outside is reduced. This further suppresses the generation of flammable substances, and more effectively imparts the physical properties required for the product to the molding composition. It is possible.
[0047] In order to further impart the physical properties required for the product to the molding composition, The content of the material is 50% by mass relative to the total of 100% by mass of the base material and the porous coordination polymer. % by mass or more, more preferably 70% by mass or more, and more preferably 90% by mass or more. More preferably, it is equal to or greater than this.
[0048] In order to further suppress the generation of gas from the base material to the outside, the inclusion of a porous coordination polymer The amount is 0.01 to 15 mass% based on 100 mass% of the total of the base material and the porous coordination polymer. % by mass, more preferably 0.1 to 10% by mass, and particularly preferably 0.5 to 5 It is more preferable that the content is expressed in mass %.
[0049] When the molding composition contains a weather resistance additive other than an antioxidant, the weather resistance additive The content is preferably 40% by mass or less based on 100% by mass of the molding composition, It is more preferably 30% by mass or less, and even more preferably 20% by mass or less. By keeping the above content within the above range, the generation of gas from the base material to the outside is prevented. This makes it possible to more effectively impart the physical properties required for the product to the molding composition. .
[0050] The molding composition may contain other optional ingredients such as inorganic fillers, plasticizers, flame retardants, etc. For example, the amount of any other optional components in the molding composition may be included in the amount that does not inhibit the solution of the problem. The content is the total of the base material, the porous coordination polymer, and the weather resistance additives other than the antioxidant. 00 parts by mass, it is preferably 50 parts by mass or less, and more preferably 30 parts by mass or less. more preferably, and even more preferably, 10 parts by mass or less.
[0051] When the molding composition of this embodiment contains the above-mentioned antioxidant, the base material in the molding composition The total content of the porous coordination polymer and the antioxidant is based on 100% by mass of the molding composition. The content is preferably 60% by mass or more and 100% by mass or less, and more preferably 70% by mass or more and 100% by mass or less. % or less, and more preferably 80% by mass or more and 100% by mass or less. By the total content being within the above range, the amount of gas derived from the base material is reduced. The external generation of fluorine is further suppressed, and the molding composition is more effectively provided with the physical properties required for the product. It is possible.
[0052] In order to further impart the physical properties required for the product to the molding composition, The content of the material is based on 100% by mass of the base material, porous coordination polymer, and antioxidant. The content is preferably 50% by mass or more, and more preferably 70% by mass or more. , and more preferably 90 mass % or more.
[0053] In order to further suppress the generation of gas from the base material to the outside, the inclusion of a porous coordination polymer The amount is 0.5% by mass relative to 100% by mass of the total of the base material, porous coordination polymer, and antioxidant. It is preferably 0.01 to 15% by mass, and more preferably 0.1 to 10% by mass. It is more preferably 0.5 to 5% by mass.
[0054] From a similar viewpoint, the content of the antioxidant is determined by the ratio of the base material, the porous coordination polymer, and the antioxidant. The content is preferably 0.01 to 10 mass%, more preferably 0.05 to 10 mass%, based on the total of 100 mass%. It is more preferably 5% by mass, and further preferably 0.1 to 3% by mass.
[0055] When the molding composition contains a weather resistance additive other than an antioxidant, the weather resistance additive The content is preferably 40% by mass or less based on 100% by mass of the molding composition, It is more preferably 30% by mass or less, and particularly preferably 20% by mass or less. By keeping the above content within the above range, the generation of gas from the base material to the outside is prevented. This makes it possible to more effectively impart the physical properties required for the product to the molding composition. .
[0056] The molding composition may contain other optional ingredients such as inorganic fillers, plasticizers, flame retardants, etc. For example, the amount of any other optional components in the molding composition may be included in the amount that does not inhibit the solution of the problem. The content is the base material, the porous coordination polymer, the antioxidant, and the weather resistance imparting additive other than the antioxidant. It is preferable that the amount of the additive is 50 parts by mass or less, and 30 parts by mass or less, based on 100 parts by mass of the total of the additive and the additive. It is more preferable that the content is 10 parts by mass or less, and further preferably 10 parts by mass or less.
[0057] (Application) The molding composition can be used not only by processing it into a molded product having a predetermined shape, but also as it is. In other words, it can be used as a coating material, a sealant, a cushioning material, or a filling material. The molding composition is prepared, for example, by selecting an appropriate plastic resin and forming a porous coordination polymer. By appropriately adjusting the amount of additives and the amount of filler, plasticizer, etc., the composition can be made to be fluid, semi-fluid, or Therefore, the present invention provides a molding assembly according to the present embodiment. The composition also includes a molded article formed from the composition. The composition having flowability can be used, for example, as a paint. Those with semi-fluidity can be used as sealing agents, for example. The molding composition can be used as a cushioning material or a stuffing. When used as a sealant, cushioning material or filling, matrix may be used as necessary. Coloring materials such as colorants and pigments can be added to the resin. In this case, for example, injection molding, compression molding, transfer molding, extrusion molding, blow molding, Calendar molding, FRP molding, lamination molding, casting, solution casting, vacuum / pressure molding, extrusion Composite molding, foam molding, thermoforming, insert molding, melt impregnation, or other suitable known molding methods In addition, there are no particular restrictions on the shape of the molded product. Instead, the shape may be any shape, such as a plate, a rod, a cylinder, a comb, or a sphere. In addition to molding the molding composition alone, it can also be combined with metals and other materials for two- or multi-color molding. It can also be done.
[0058] Another embodiment of the present invention is a method for manufacturing a gypsum lath from the group consisting of plastic resins, rubbers, and sealants. A porous coordination polymer containing metal ions and organic ligands is formed on one or more selected base materials. The method suppresses the generation of gas originating from the base material by blending molecules. The porous coordination polymer and the base material each satisfy the following condition (A) or (B): It is a way to fulfill it. (A) when the acid dissociation constant of the gas derived from the base material is 16.6 or less, the porous The radius of the metal ion in the coordination polymer is 62×10 -12 m or less. (B) when the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous The radius of the metal ion in the coordination polymer is 68×10 -12 m or more.
[0059] The present invention will be described in more detail below using examples and comparative examples. The examples are not limiting in any way.
[0060] [Example 1] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g 100g of porous coordination polymer and 50g of aromatic polyamide resin ("RA230NK" product of Mitsui Chemicals, Inc.) ") is compounded and mixed at 320℃ in a lab plastomill device, and then molded. A composition was prepared. The prepared molding composition was molded in a hot press under heating conditions of 320°C and 10 MPa to produce a thickness of 1. A compact on a 0 mm plate was prepared.
[0061] [Example 2] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was produced in the same manner as in Example 1.
[0062] [Example 3] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as described above.
[0063] [Example 4] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was produced in the same manner as in Example 1.
[0064] [Example 5] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Other than that, a molded body was produced in the same manner as in Example 1.
[0065] [Example 6] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Other than that, a molded body was produced in the same manner as in Example 1.
[0066] [Example 7] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as described above.
[0067] [Example 8] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 1.
[0068] [Example 9] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 1, except that a molded body having a thickness of 100 mm or less was used.
[0069] [Example 10] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 1, except that a powder ("Zif-8") was used.
[0070] [Example 11] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Example 1 except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as described above.
[0071] [Example 12] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g The porous coordination polymer and 50 g of polyamide 6 resin ("CM1007" by Toray Industries, Inc.) were mixed for 2 The mixture was compounded and mixed at 80°C in a Lab Plastomill device to prepare a molding composition. Ta. The prepared molding composition was molded in a hot press under heating conditions of 280°C and 10 MPa to obtain a thick molded product. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0072] [Example 13] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was produced in the same manner as in Example 12.
[0073] [Example 14] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 2.
[0074] [Example 15] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was produced in the same manner as in Example 12.
[0075] [Example 16] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Other than that, a molded body was produced in the same manner as in Example 1.
[0076] [Example 17] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Other than that, a molded body was produced in the same manner as in Example 12.
[0077] [Example 18] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 2.
[0078] [Example 19] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 12.
[0079] [Example 20] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 12, except that a molded body having a thickness of 100 mm or less was used.
[0080] [Example 21] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 12, except that a powder ("Zif-8") was used.
[0081] [Example 22] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in 12.
[0082] [Example 23] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g of porous coordination polymer and 50g of polyphenylene sulfide resin (Polyplastics Corporation) The product (1140A6) is compounded and processed at 300°C using a lab plastomill device. The mixture was mixed to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 300°C and 10 MPa to obtain a thick molded product. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0083] [Example 24] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was produced in the same manner as in Example 23.
[0084] [Example 25] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 2 was used except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 3.
[0085] [Example 26] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was produced in the same manner as in Example 23.
[0086] [Example 27] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 23.
[0087] [Example 28] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 23.
[0088] [Example 29] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 2 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 3.
[0089] [Example 30] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 23.
[0090] [Example 31] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 23, except that a molded body having a thickness of 100 mm or less was used.
[0091] [Example 32] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 23, except that a powder ("Zif-8") was used.
[0092] [Example 33] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 23.
[0093] [Example 34] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g The porous coordination polymer and 50 g of ABS resin (Toray Industries, Inc. product "700-314") were heated at 240°C. The mixture was compounded and mixed to produce a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 240°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0094] [Example 35] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was produced in the same manner as in Example 34.
[0095] [Example 36] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 3 was used except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 4.
[0096] [Example 37] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was produced in the same manner as in Example 34.
[0097] [Example 38] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 34.
[0098] [Example 39] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 34.
[0099] [Example 40] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 3 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 4.
[0100] [Example 41] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 34.
[0101] [Example 42] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 34, except that a molded body having a thickness of 100 mm or less was used.
[0102] [Example 43] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 34, except that a powder ("Zif-8") was used.
[0103] [Example 44] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 34.
[0104] [Example 45] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g 100g of porous coordination polymer and 50g of polyphenylene oxide resin (XYRON 100V" was compounded and mixed at 320°C to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 320°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0105] [Example 46] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 45.
[0106] [Example 47] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 4 was used except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 5.
[0107] [Example 48] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 45.
[0108] [Example 49] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 45.
[0109] [Example 50] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 45.
[0110] [Example 51] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 4 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 5.
[0111] [Example 52] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 45.
[0112] [Example 53] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 45, except that a molded body containing the above-mentioned fluororesin was used.
[0113] [Example 54] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 45, except that a powder ("Zif-8") was used.
[0114] [Example 55] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 45.
[0115] [Example 56] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g of porous coordination polymer and 50 g of polybutylene terephthalate resin (Mitsubishi Chemical Corporation "5010-CR2") at 120°C and mixed to prepare a molding composition. Made. The prepared molding composition was molded in a hot press under heating conditions of 120°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0116] [Example 57] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 56.
[0117] [Example 58] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 5 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 6.
[0118] [Example 59] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 56.
[0119] [Example 60] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 56.
[0120] [Example 61] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 56.
[0121] [Example 62] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 5 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 6.
[0122] [Example 63] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 56.
[0123] [Example 64] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 56, except that a molded body having a thickness of 100 mm or less was used.
[0124] [Example 65] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 56, except that a powder ("Zif-8") was used.
[0125] [Example 66] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 56.
[0126] [Example 67] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g 100 g of porous coordination polymer and 50 g of polyvinyl chloride resin (GR -800-T" was compounded and mixed at 200°C to prepare a molding composition. . The prepared molding composition was molded in a hot press under heating conditions of 200°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0127] [Example 68] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 67.
[0128] [Example 69] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 6 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 7.
[0129] [Example 70] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 67.
[0130] [Example 71] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 67.
[0131] [Example 72] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 67.
[0132] [Example 73] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 6 was repeated except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 7.
[0133] [Example 74] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 67.
[0134] [Example 75] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 67, except that a molded body having a thickness of 100 mm or less was used.
[0135] [Example 76] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 67, except that a powder ("Zif-8") was used.
[0136] [Example 77] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in 67.
[0137] [Example 78] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g The porous coordination polymer and 50g of PTFE resin (Daikin Industries, Ltd. product "M-12") were mixed for 34 h. The mixture was compounded and mixed at 0° C. to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 340°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0138] [Example 79] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 78.
[0139] [Example 80 Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 7 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in Example 8.
[0140] [Example 81] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 78.
[0141] [Example 82] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 78.
[0142] [Example 83] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 78.
[0143] [Example 84] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 7 was repeated except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in Example 8.
[0144] [Example 85] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 78.
[0145] [Example 86] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 78, except that a molded body having a thickness of 100 mm or less was used.
[0146] [Example 87] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 78, except that a powder ("Zif-8") was used.
[0147] [Example 88] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 78.
[0148] [Example 89] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g 100g of porous coordination polymer and 50g of polycarbonate resin (Mitsubishi Chemical Corporation product "S-3000 ") was compounded and mixed at 300°C to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 300°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0149] [Example 90] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 89.
[0150] [Example 91] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 8 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in Example 9.
[0151] [Example 92] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 89.
[0152] [Example 93] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 89.
[0153] [Example 94] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 89.
[0154] [Example 95] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 8 was repeated except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in Example 9. [Example 96]
[0155] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 89.
[0156] [Example 97] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded article was produced in the same manner as in Example 89, except that a molded article containing the above-mentioned fluororesin was used.
[0157] [Example 98] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 89, except that a powder ("Zif-8") was used.
[0158] [Example 99] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 89.
[0159] [Example 100] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g of porous coordination polymer and 50g of polyacetal resin (Polyplastics Corporation product "M -90-44") was compounded and mixed at 210°C to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 210°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0160] [Example 101] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded article was produced in the same manner as in Example 100.
[0161] [Example 102] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in Example 00.
[0162] [Example 103] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded article was produced in the same manner as in Example 100.
[0163] [Example 104] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Other than that, a molded body was produced in the same manner as in Example 100.
[0164] [Example 105] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Other than that, a molded body was produced in the same manner as in Example 100.
[0165] [Example 106] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in Example 00.
[0166] [Example 107] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 100.
[0167] [Example 108] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded article was produced in the same manner as in Example 100, except that a molded article containing the above-mentioned fluororesin was used.
[0168] [Example 109] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 100, except that a powder ("Zif-8") was used.
[0169] [Example 110] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 100.
[0170] [Example 111] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g 100g of porous coordination polymer and 50g of urethane elastomer (BASF product "Elaston C" 80A") was compounded and mixed at 280°C to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 280°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0171] [Example 112] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 111.
[0172] [Example 113] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in Example 11.
[0173] [Example 114] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 111.
[0174] [Example 115] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 111.
[0175] [Example 116] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 111.
[0176] [Example 117] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in Example 11.
[0177] [Example 118] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was produced in the same manner as in Example 111.
[0178] [Example 119] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded article was produced in the same manner as in Example 111, except that a molded article containing the above-mentioned fluororesin was used.
[0179] [Example 120] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 111, except that a powder ("Zif-8") was used.
[0180] [Example 121] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 111.
[0181] [Example 122] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g The porous coordination polymer and 50g of EPDM rubber (JSR Corporation product "JSR EP331") were mixed for 1 The mixture was compounded and mixed at 80° C. to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 180°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0182] [Example 123] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 122.
[0183] [Example 124] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in 22.
[0184] [Example 125] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 122.
[0185] [Example 126] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 122.
[0186] [Example 127] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 122.
[0187] [Example 128] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in 22.
[0188] [Example 129] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was prepared in the same manner as in Example 122.
[0189] [Example 130] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded body was produced in the same manner as in Example 122, except that a molded body containing the above-mentioned fluororesin was used.
[0190] [Example 131] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 122, except that a powder ("Zif-8") was used.
[0191] [Example 132] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 122.
[0192] [Example 133] The metal ion is titanium ion (oxidation number 4, ionic radius 42 pm), and the organic ligand is tetramethyl ether. A porous coordination polymer composed of tetraethyl phthalic acid ("MIL-125(Ti)") was used. 0.5g The porous coordination polymer and 50 g of SBR rubber (JSR HPR850, a product of JSR Corporation) were heated at 150°C. The mixture was compounded and mixed at 0.5° C. to prepare a molding composition. The prepared molding composition was molded in a hot press under heating conditions of 150°C and 10 MPa. A plate-shaped compact having a thickness of 1.0 mm was prepared.
[0193] [Example 134] Instead of MIL-125 (Ti), aluminum ion (oxidation number 3, ionic radius 54 pm), In addition to using a porous coordination polymer ("Al-PCP-F") composed of fumaric acid as the functional ligand, A molded body was prepared in the same manner as in Example 133.
[0194] [Example 135] Instead of MIL-125(Ti), iron ion (oxidation number 3, ionic radius 55 pm) and organic ligand The same procedure as in Example 1 was repeated except that a porous coordination polymer composed of trimesic acid ("Fe-BTC") was used. A molded body was prepared in the same manner as in Example 33.
[0195] [Example 136] Instead of MIL-125(Ti), chromium ion (oxidation number 3, ionic radius 63 pm) and organic ligand As a material for the porous coordination polymer, we used a porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid. A molded body was prepared in the same manner as in Example 133.
[0196] [Example 137] Instead of MIL-125(Ti), nickel ion (oxidation number 2, ionic radius 68 pm), organic coordination The following porous coordination polymer ("Mil-101(Cr)") composed of terephthalic acid was used as a molecule. Except for the above, a molded body was produced in the same manner as in Example 133.
[0197] [Example 138] Instead of MIL-125 (Ti), zirconium ion (oxidation number 4, ionic radius 72 pm), organic The following porous coordination polymer (Uio-66) composed of terephthalic acid was used as the ligand. Except for the above, a molded body was produced in the same manner as in Example 133.
[0198] [Example 139] Instead of MIL-125(Ti), copper ions (oxidation number 2, ionic radius 73 pm) and organic ligands The same procedure as in Example 1 was used except that a porous coordination polymer composed of trimesic acid ("Cu-BTC") was used. A molded body was prepared in the same manner as in Example 33.
[0199] [Example 140] Instead of MIL-125(Ti), zinc ion (oxidation number 2, ionic radius 74 pm), organic ligand and The only exception was the use of a porous coordination polymer ("Zif-8") composed of 2-imidazole. A molded body was prepared in the same manner as in Example 133.
[0200] [Example 141] Instead of MIL-125(Ti), platinum ion (oxidation number 2, ionic radius 80 pm), organic coordination The porous coordination polymer (Pt-PCP) composed of 4,4′-bipyridine and ethyleneamine was used as a A molded article was produced in the same manner as in Example 133, except that a molded article containing the above-mentioned fluororesin was used.
[0201] [Example 142] Instead of MIL-125(Ti), lanthanum ion (oxidation number 3, ionic radius 103 pm), organic coordination Porous coordination polymers composed of 1,3,5-tris(4-carboxyphenyl)benzene as molecules A molded body was produced in the same manner as in Example 133, except that a powder ("Zif-8") was used.
[0202] [Example 143] Silver ion (oxidation number 1, ionic radius 115 pm) instead of MIL-125(Ti) as an organic ligand Examples except that a porous coordination polymer composed of di-p-xylylene ("Ag-PCP") was used A molded body was prepared in the same manner as in Example 133.
[0203] [Comparative Example 1] A molded body was produced in the same manner as in Example 1, except that the porous coordination polymer was not used.
[0204] [Comparative Example 2] A molded body was produced in the same manner as in Example 12, except that the porous coordination polymer was not used.
[0205] [Comparative Example 3] A molded body was produced in the same manner as in Example 23, except that the porous coordination polymer was not used.
[0206] [Comparative Example 4] A molded body was produced in the same manner as in Example 34, except that the porous coordination polymer was not used.
[0207] [Comparative Example 5] A molded body was produced in the same manner as in Example 45, except that the porous coordination polymer was not used.
[0208] [Comparative Example 6] A molded body was produced in the same manner as in Example 56, except that the porous coordination polymer was not used.
[0209] [Comparative Example 7] A molded body was produced in the same manner as in Example 67, except that the porous coordination polymer was not used.
[0210] [Comparative Example 8] A molded body was produced in the same manner as in Example 78, except that the porous coordination polymer was not used.
[0211] [Comparative Example 9] A molded body was produced in the same manner as in Example 89, except that the porous coordination polymer was not used.
[0212] [Comparative Example 10] A molded body was produced in the same manner as in Example 100, except that the porous coordination polymer was not used.
[0213] [Comparative Example 11] A molded body was produced in the same manner as in Example 111, except that the porous coordination polymer was not used.
[0214] [Comparative Example 12] A molded body was produced in the same manner as in Example 122, except that the porous coordination polymer was not used.
[0215] [Comparative Example 13] A molded body was produced in the same manner as in Example 133, except that the porous coordination polymer was not used.
[0216] (Evaluation of gas adsorption rate) The gas adsorption rate of the samples of the examples and comparative examples was evaluated by the following method. Ta. Pyrolysis gas chromatograph mass spectrometer (product name "7890A / 5975C") at the same temperature as the kneading temperature of each resin or rubber, and the generated gas components The gas components were separated and analyzed by mass spectrometry. The results of the mass spectrometry were compared with the library to identify the gas components. The amount of gas generated was calculated from the height of each peak in the chromatogram. An example is shown in Figure 1. In this analysis, the gas components of the substances that were identified by mass spectrometry were Of these, substances that account for up to 90% of the total gas generation volume were targeted.
[0217] The gas adsorption rate was calculated from the following formula.
number
[0218] From the results, it was found that gas components and porous polymers evolved during the melting of resins and rubbers As a result of thorough investigation of the physical properties of the molecules, the following relationship was found for the acid dissociation constants of the gas components: I was able to get it out.
[0219] First, the examples and comparative examples prepared are shown in Tables 1 to 5. The gas amounts of the comparative examples are shown in Table 6. The results are shown for each resin in Tables 7 to 19. In Examples 1 to 143, the gas adsorption rate was 15% or more. The relationship between the acid dissociation constant of the gas component and the ionic radius of the porous coordination polymer is shown in Figure 1. The relationship between the acid dissociation constant of a gas component with an adsorption rate of less than 15% and the ionic radius of a porous coordination polymer is shown. As shown in FIG. 2, in all the examples, the adsorption rate of each gas component was 15% or more. It was found that there is the following relationship between the acid dissociation constant and ionic radius of the gas components: Condition (A) If the acid dissociation constant of the generated gas component is 16.61 or less, the ionic radius is 62p Combinations of porous coordination polymers with metal atoms of m or less are effective. Condition (B) If the acid dissociation constant of the generated gas component is 17.00 or more, the ionic radius is 69 pm Combinations of the above-mentioned metal atoms and porous coordination polymers are effective.
[0220] The above conditions are shown shaded in Figure 2. In addition, as shown in Figure 2, the gas adsorption rate is less than 15%, which is an inappropriate combination that does not satisfy the above conditions. The combinations that are full do not fall into the shaded areas.
[0221] The adsorption of a substance into a porous coordination polymer is carried out by holding the adsorbed substance in the pores of the porous coordination polymer. In particular, the intermolecular forces between the metal atoms and the adsorbed substance are involved in the retention of the adsorbed substance. It is thought that two types of forces, the induction effect and the resonance effect, are at work in the adsorption due to intermolecular forces. The bond involved in the inductive effect is a polarized bond, and the material in which the charge imbalance occurs As a measure of the charge bias of the adsorbed substance, we focused on the acid dissociation constant. This is a numerical representation of the dissociation reaction in which hydrogen ions are released from the atom. A low value indicates that the electron The charge imbalance increases, and the charge becomes biased. The charge imbalance is the electric field, which is the strength of attraction of electrons. When the ionic radius of the metal atoms that compose the porous coordination polymer is small, the electronegativity depends on the electronegativity. Therefore, the electronegativity increases for adsorbed substances with wide electron orbits. It is believed that porous coordination polymers with metal atoms with high degree of resonance are effective. The bond involved in the effect is caused by the delocalization of electrons. It can be thought of as a substance in which there is no charge imbalance, like a substance. Therefore, the adsorbed porous coordination polymer is a porous coordination polymer. The metal atoms that make up the compound have a low electronegativity and a large ionic radius that is weak in attracting electrons. We believe that a metal atom with a low molecular weight is effective.
[0222] Therefore, in order to reduce the amount of gas generated when resins and rubbers are melted, the above conditions ( Acid dissociation constants of gas components satisfying A) and (B) and ionic radii of metal atoms in porous coordination polymers It is required that: [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] Each box in Table 6 above lists the symbol, substance name, acid dissociation constant, and amount of gas evolved, in that order. In the gas adsorption rate (%) columns of Tables 7 to 19 below, the acid dissociation constant is listed after each substance name. . [Table 7] [Table 8] [Table 9] [Table 10] [Table 11] [Table 12] [Table 13] [Table 14] [Table 15] [Table 16] [Table 17] [Table 18] [Table 19] [Industrial Applicability]
[0223] The molding composition of this embodiment is used in office automation equipment, storage media devices such as hard disks, and semiconductor-related It is suitable as a material for precision moldings applied to infrastructure equipment such as equipment, motor equipment, and water-related components. It can be used appropriately.
Claims
1. Porous coordination polymers containing metal ions and organic ligands, plastic resins, rubbers and one or more base materials selected from the group consisting of a sealing material, The coordination polymer and the base material satisfy the following condition (A) or (B), respectively: composition. (A) When the acid dissociation constant of the gas derived from the base material is 16.6 or less, the porous The radius of the metal ion in the coordination polymer is 62 x 10 -12 m or less. (B) When the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous The radius of the metal ion in the coordination polymer is 68 x 10 -12 m or more.
2. The metal ion is Ag(I), Al(III), Be(II), Ca(II), Cd (II), Ce(III), Co(III), Co(II), Cr(III), Cu(I I), Cu(I), Dy(III), Er(III), Eu(III), Fe(III) , Fe(II), Ga(III), Gd(III), Ho(III), In(III), Li(I), Mg(II), Mn(III), Mo(III), Nd(III), Ni( II), Sc(III), Sm(II I), Sn(II), Tb(III), Ti(IV)Tm(III), V(III), W (IV), Y (III), Yb (III), Zn (II), Pd (II), Au (I), One or more selected from the group consisting of Tl(I), Hg(I), Pt(I) and Zr(IV). The molding composition of claim 1 , wherein
3. A molded article of the molding composition according to claim 1 or 2.
4. One or more base materials selected from the group consisting of plastic resins, rubbers, and sealing materials By blending a porous coordination polymer containing metal ions and organic ligands into the silicon material, A method for suppressing gas generation originating from the base material, comprising the steps of: and a method in which the base material satisfies the following condition (A) or (B), respectively: (A) When the acid dissociation constant of the gas derived from the base material is 16.6 or less, the porous The radius of the metal ion in the coordination polymer is 62 x 10 -12 m or less. (B) When the acid dissociation constant of the gas derived from the base material is 17.0 or less, the porous The radius of the metal ion in the coordination polymer is 68 x 10 -12 m or more.
Citation Information
Patent Citations
Production of polyphenylene sulfide
JP1987197422A
Molded article of polyarylene thioether and use thereof
JP1988207827A
Polyarylene sulfide-based composition
JP2016132710A
Resin composition and method for producing the same
JP2017190426A
Polyarylene sulfide resin composition
JP3235035B2